Effectiveness of the Job Promotion System for Teachers in Improving Achievement Motivation from the Point of View of Elementary Stage Teachers in the Directorate of Education of Mafraq - Anajrah, Fawaz Ahmed (Journal of Educational and Psychological Sciences, 2022)
This study aimed to figure out the effectiveness of the job promotion system for teachers (teacher ranks) in improving the achievement motivation from the point of view of teachers in the directorate of education of Mafraq district. To achieve the objectives of the study, the descriptive, analytical approach was adopted through preparing and distributing questionnaires to a sample consisting of (359) male and female teachers for the elementary stage in Mafraq. After conducting the statistical analysis through the (SPSS), it was found that the level of the effectiveness of the job promotion system among the teachers (teacher ranks) in the directorate of education of Mafraq from the teachers’ point of view had a medium mean (3.25 out of 5) with a medium effectiveness. At the domain level, the commitment to the promotion criteria got an average of (3.43) with a (high) effectiveness followed by the promotion goals with a mean of (3.17) and the application of the foundations of promotion principles with a mean of (3.15), both with a (medium) rating. The field of the achievement motivation among the primary school teachers got a mean of (3.58) by a (high) evaluation degree. Furthermore, the findings also showed that the relationship between the effectiveness of the job promotion system and the achievement motivation was (0.56) reflecting a medium correlation coefficient, which is direct and statistically significant at sig. (α≥0.05). Based on the results, the researcher recommends relying on the supervisors’ evaluation of teachers, applying a system of salaries and incentives appropriate to the nature of teachers’ work, and developing teachers’ performance with diversifying the activities and events of the training programs in addition to suggestions for future studies.